Camarillo State Hospital Visiting Request
This document is a visiting request form needed for admission to enter the Camarillo State Hospital facility. This document requested information about the patient's name, the relationship with the patient, the address, and the phone number. The form also contains a small message to encourage the relatives and friends of the patient's to visit as frequently as possible as well asking for assistance in keeping the Camarillo State Hospital clean.